Rare Coagulation Factor Deficiencies: Multicenter Experience With 188 Cases - Veysel Gök; Esra Pekpak Şahinoğlu; Hüseyin Tokgöz; Fatma Türkan Mutlu; Can Acıpayam; Kamuran Karaman; Defne Ay Tuncel; Ayşe Ceyda Ören; Ayşe Şimşek; Bilal Arslan; Hatice Beyza Ünal; Alper Özcan; et al. (Çocuk Dergisi)
Objective: Rare factor deficiencies are a group of autosomal recessive bleeding disorders (with the exception of dysfibrinogenemia), which are characterized by the deficiency or dysfunction of one or more coagulation factors (F)I, FII, FV, FV+FVIII, FVII, FX, FXI, FXII, and FXIII.Materials and Methods: 188 patients with a rare factor deficiency from seven distinct pediatric hematology centers in Turkey were obtained for the study. Results: 60 (31.9%) patients had a family history of bleeding. Consanguinity was detected in 85 patients (45.2%). 128 patients (68.1%) were symptomatic; the most common bleeding symptom was epistaxis (34.6%) and followed by the bleeding of skin (19.1%), oral cavity (16.1%), soft tissue (8%), central nervous system (CNS) (6.2%), uterine (4.9%), joint (3.7%), gastrointestinal system (GIS) (3.7%), and urinary system (US) (3.7%). The first bleeding sites consist of nose (39%), CNS (10.9%), oral cavity (10.9%), skin (10.9%), umbilical cord (10.2%), GIS (5.5%), US (5.5%), heel (4.7%), and musculoskeletal system (2.3%). CNS hemorrhage was the most common in fibrinogen (n:4), FVII (n:6), and FX (n:2) deficiency, umbilical cord bleeding was the most common in fibrinogen (n:3) and FXIII (n:7) deficiency, heel bleeding was frequently seen in fibrinogen (n:6) deficiency. The life-threatening bleedings were CNS (n:27, 77.1%), GIS (n:7, 20%), and iliopsoas (n:1, 2.9%), respectively. The reasons leading to the diagnosis were bleeding (57.4%), preoperative screening (15.4%), incidental (15.4%), family history (6.4%), and postoperative bleeding (5.3%). 2/5 FXII deficiency patients had mild bleeding symptoms. Conclusion: As bleeding disorders are somehow a rare group of disorder, early diagnosis and treatment are critical to reduce the high morbidity and mortality